TRADE EFFICIENCY IN A MARKET ECONOMY AND WAYS TO IMPROVE IT - Artikov Zokir Sayfiddinovich; Egamkulov Davlatbek Bahodir o’g’li (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: This article examines the issue of trade efficiency in a market economy and suggests ways to improve it. We analyze the main factors influencing trade efficiency, such as competition, innovation, regulation and technological progress. The article also discusses strategies and measures that can be taken to improve trading efficiency in today's market economy.